2017
DOI: 10.1155/2017/8706921
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of PEI and PVP-Stabilized Gold Nanoparticles on Equine Platelets Activation: Potential Application in Equine Regenerative Medicine

Abstract: The aim of this work was to assess the effect of different stabilizing agents, for example, polyethylenimine (PEI) and polyvinylpyrrolidone (PVP), on gold nanoparticles (AuNPs) and their influence on equine platelet activation and release of particular growth factors. The gold nanoparticles were produced by chemical reduction of chloroauric acid. UV-Vis spectroscopy confirmed the presence of gold nanoparticles in investigated solutions. The AuNPs were incubated with whole blood at various concentrations. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Up to now, PVP has been used in the pharmaceutical and biomedical fields to develop different drug delivery systems, such as oral, topical, transdermal, and ocular administration. Besides, PVP is also useful in the delivery of genes [8][9][10][11][12] or can be coupled with metal particles for regenerative medicine [13][14][15] and targeted-delivery [16,17]. Therefore, PVP results to also be a very versatile polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, PVP has been used in the pharmaceutical and biomedical fields to develop different drug delivery systems, such as oral, topical, transdermal, and ocular administration. Besides, PVP is also useful in the delivery of genes [8][9][10][11][12] or can be coupled with metal particles for regenerative medicine [13][14][15] and targeted-delivery [16,17]. Therefore, PVP results to also be a very versatile polymer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the polymer length is too short, the nanoparticles would not be covered with the polymer layer completely, leading to their agglomeration. Furthermore, the high hydrophobicity of the PEG prevents the adsorption on the nanocurcumin particle surface for steric stabilization [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The group has demonstrated that QCM-D is more sensitive than the traditional LTA when investigating NP-platelet interactions (69, 99) and found that PEGylation of gold NPs improves their platelet compatibility (15). However, the use of polyethyleneimine (PEI) and polyvinylpyrrolidone (PVP) conjugated NPs can induce platelet activation as revealed by the formation of numerous filopodia and degranulation in equine platelets (70). This effect may be related to the adsorption of fibrinogen onto the NPs surface (5) and could be even more obvious if polyacrylic acid (PAA)-conjugated gold nanoparticles are exposed to platelets as PAA binds to and induce conformational changes of fibrinogen (100) that could potentially have a greater impact on the hemocompatibility of those NPs.…”
Section: Metallic Nanoparticles-platelets Interactionsmentioning
confidence: 99%